Databases of biological collection: organization of associated information - S. V. Buikin; Ye. Yu. Bragina; L. A. Koneva; V. P. Puzyryov (Бюллетень сибирской медицины)
The review discusses problem of organization and storage of associated information for biological collection. Basic principles of database structure development are presented. Databases for biological collections and biobanks in Russiaand other countries are reviewed. Structure of database of Biobank of Institute of Medical Genetics SB RAMS is described.